Government support towards environmental volunteering participation - Alya Nasuha Abdul Rahman,; Norshariani Abd Rahman,; Shamsul Azhar Yahya, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Environmental volunteering is a form of unpaid helping behaviour that benefits the environment and a prosocial action that need support from government to ensure the objectives of environmental volunteerism reach its goal. Volunteerism has been a key of the global environmental movement by mobilizing communities in the world to help address environmental problems as protecting the environment is the responsibility of everyone in the community. NGOs act as bridge that linked the government support and the communities. This study is a mixed study that explored the government support towards environmental volunteering participation by analysing the data from verbatim responses of 10 individuals and questionnaire answered by 119 respondents that have participated in environmental volunteering activities. The results reveal that there are two elements of the government support towards environmental volunteering participation in Malaysia which is through incentives and education. The mean for this analysis is 6.95 with standard deviation of 2.404. The findings of the study indicate that environmental volunteerism should be a requirement in environmental education as it is seen as an encouragement for environmental conservation practices and volunteerism.